Recycling of solar panel : upcycling as silicon anode battery - Lin, Xue (Nanyang Technological University, 2022)
Management of the end of life (EOL) photovoltaic (PV) panels will be an environmental problem due to the limited lifespans of PV modules. Thus, researchers are actively looking into various methods to recycle the EOL panels. In this paper, I will discuss the use of ball milling via different parameters to achieve nanosize silicon particles from 325 mesh silicon powder and leached silicon solar wafer. Different duration of ball milling will be investigated in this paper in order to achieve the most efficient timing to attain nanosize silicon particles. The result from scanning electron microscopy – energy-dispersive x-ray spectroscopy, particle size analyzer as well as Brunauer-Emmett-Telle is used to confirm the size of silicon particles after every milling process. Variable Solid to liquid (S/L) ratio will also be looked into for attaining the best slurry viscosity of ball-milled silicon powder for assembly of battery. The viscosity of different S/L was measured, and comparison with screen printing results of slurry on a copper sheet was compared.